Expression and localization of grass carp pkc-θ (protein kinase C theta) gene after its activation. Issue 87 (April 2019) - Mehjabin, Rumana; Chen, Liangming; Huang, Rong; Zhu, Denghui; Yang, Cheng; Li, Yongming; Liao, Lanjie; He, Libo; Zhu, Zuoyan; Wang, Yaping
Abstract: Haemorrhagic disease caused by grass carp reovirus (GCRV) can result in large-scale death of young grass carp, leading to irreparable economic losses that seriously affect large-scale breeding. Protein kinase C (PKC, also known as PRKC) represents a family of serine/threonine protein kinases that includes multiple isozymes in many species. Among these, PKC-θ (PKC theta, also written as PRKCQ) is a novel isoform, mainly expressed in T cells, that is known to be involved in immune system function in mammals. To date, no research on immunological functions of fish Pkc-θ has been reported. To address this issue, we cloned the grass carp pkc-θ gene. Phylogenetic and syntenic analysis showed that this gene is the most evolutionarily conserved relative to zebrafish. Real-time quantitative PCR (RT-qPCR) indicated that pkc-θ was expressed at high levels in the gills and spleen of healthy grass carp. Infection with GCRV down regulated pkc-θ expression in the gills and spleen. Gene products that function upstream and downstream of pkc-θ were up regulated in the gill, but were down-regulated in the spleen. These results suggest that direct or indirect targeting of pkc-θ by GCRV may help the virus evade host immune defences in the spleen. Phorbol ester (PMA) treatment of Jurkat T cells induced translocation of grass carp Pkc-θ from the cytoplasm to the plasma membrane. This response to PMA suggests evolutionary conservation of an immune response function in fish Pkc-θ, as well as conservation of its sequence and structural domains. This study expanded our knowledge of the fish PKC gene family, and explored the role of pkc-θ in function of the grass carp immune system, providing new insights which may facilitate further studies of its biological functions. Highlights: Grass carp Pkc-θ was structurally conserved compared with other species. Grass carp pkc-θ was enriched in the gill and spleen. Grass carp pkc-θ and its related genes underwent similarily significant changes in gill and spleen after GCRV infection. Phorbol ester (PMA) made grass carp Pkc-θ translocated from- cytoplasm to the membrane in Jurkat T cells.